Tanggung Jawab Etika Profesi Hukum untuk Menjaga Kerahasiaan serta Keamanan Data di Era Digitalisasi - Sulistiawati; Muh Arbai Santoso; Nita Yunita; Rendhi Renaldhi; Siti Nur Ambarini (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of digital technology brings new challenges to the practice of the legal profession, particularly for advocates. Professional ethics, previously established within the context of conventional practice, are now faced with new issues, such as the use of social media for self-promotion and the risk of client personal data leaks. This paper discusses violations of the advocate code of ethics in the digital context and the importance of protecting personal data as part of the principle of legal professional confidentiality. Using normative methods and a literature review, this article analyzes the legal provisions governing the advocate code of ethics, including legal foundations such as Law No. 18/2003 concerning Advocates, the Indonesian Financial and Investment Commission (KEAAI), and Law No. 27/2022 concerning data privacy and security. This study highlights the importance of strengthening the oversight system for professional ethics, encouraging increased digital literacy capacity among advocates, and urging the establishment of a responsive and effective oversight mechanism to address the dynamics of professional ethics in the digital era. Efforts to maintain the integrity of the legal profession and build public trust are inseparable from a commitment to protecting personal data and enforcing ethical norms.